Atypical cellular blue nevus: A case report and review of literature - Shi H; Fidelis C; Zou Y; Liang J; Huang B; Zhou B; Liang Z (JCIMCR, 2022)
Blue nevi are benign neoplasms of many variants which have several similar histological, clinical and immunochemical features. The two most frequent types are dendritic/common blue nevus and cellular blue nevus. Atypical blue nevus is a rare variant of cellular blue nevus whose characteristics are usually confused with malignant blue nevus/malignant melanoma which arise in a cellular blue nevus. Our paper describes a case of a 59-year-old woman who presented with a pigmented lesion in her right gluteal region which started itching and slowly grew in the last 20 years. After surgical resection, histopathological examination showed a nodule which had features that were consistent with atypical cellular blue nevus.